Comparative Study of Haemodynamic Status and Arrhythmia between Combined Epidural with General Anaesthesia and General Anaesthesia alone in Off-pump Coronary Artery Bypass (OPCAB) Surgery - Kundu, Ranadhir Kumar; Beg, Abdul Khaleque; Hossain, Shahadat; Haque, Naimul; Mahafuddoza, M; Chowdhury, Abu Yusuf Fazle Elahi (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objectives: To find out if combined general anaesthesia (GA) with high thoracic epidural anaesthesia (HTEA) was better in controlling haemodynamic condition and reducing incidences of arrhythmia during induction of GA and during positioning and handling of the heart itself by the surgeons. Materials and Method: Forty (40) patients of 40-65 yrs age were randomly selected and divided in two groups (group A, n= 20: combined HTEA and GA- study group, group B, n= 20: GA alone- control group). Group A received HTEA introduced through an indwelling epidural catheter at C7-T1 or T1-T2 interspace. Lignocaine (1%) 5 ml and Bupivacain (0.25%) 5ml with Fentanyl 10 mg was given through the catheter as bolus followed by Bupivacain (0.25%) 5ml with Fentanyl 10 mg was given at 2 hours interval. General anaesthesia was induced and maintained in a standardized manner for all patients of both the groups. The parameters monitored were Heart Rate (HR), Arterial Blood Pressure (ABP), and Electrocardiogram (ECG - arrhythmia and ST changes), Oxygen saturation (SpO2) and Central Venous Pressure (CVP) during the procedure Results: Induction of GA was smoother and with fewer blood pressure peaks in all patients of group A. They demonstrated a stable haemodynamic status throughout operation in general and during positioning of the heart and bypass grafting in particular. Incidences and severity of cardiac arrhythmias were also less during these periods. Conclusion: Combined HTEA-GA technique for OPCAB procedure is safe and affords to achieve stable haemodynamic status during induction of GA. It also allows reducing incidence of arrhythmias during cardiac position and grafting. Regarding the above qualities, group A appeared superior to group B. DOI: 10.3329/jbcps.v26i3.4193 J Bangladesh Coll Phys Surg 2008; 26: 116-120